Cómo Elaborar El Modelo De Educación Smart Del Español - Sangyoung, Mah, (European Scientific Journal, ESJ, 2017)
In this mobile society, young students mostly spend their 24 hours with mobile devices, especially smartphones, which can be the best tools for the education of Spanish language. Accordingly, it is inevitable to elaborate smart-learning classes based on mobile technology, because students react very positively and actively toward this type of classes. But until now only few Spanish professors have utilized smart devices in their teaching. Given the situation, this study aims to suggest the ways to build up the comprehensive model of Spanish smart education and the efficient methods to elaborate smart classes. To achieve this purpose, we tested various programs and applications as well as preparing specialized contents to be loaded on the online websites. The contents are encoded into several different types optimized with each smart devices such as smartphone, tablet PC, and ones other than PC. In this system, we first offer learning contents to students through smart devices and, afterward, give feedbacks to them in inclass lecture. The combination of smart teaching and in-class education enables us to complement the drawbacks that either type of teaching methods entails. The education of Spanish has been practiced mostly through a person-to-person contact so far, but the parallel use of smart education is expected to increase the efficiency in our foreign language education. Once smart education contents are well-developed, a majority of students may benefit an easy access to the stored contents regardless of time and place. In conclusion, we suggest that it is the best solution for the education of Spanish to combine smart-learning and in-class lecture.